The Evaluation of Human Dry Mandible Motion on Linear Measurements and Quality Assessment Via Cone Beam Computed Tomography – in vitro Study - Arash Dabaghi; Mehdi Pur Mehdi Boroujeni; Soheila Bayati; Tahereh Zaheri (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective: the role of cone beam CT in imaging of the oral and maxillofacial region is well known and its indications and possibilities are still increasing. one of the major problems remaining to be solved is the unwanted movements of the patient during the scanning procedure. The purpose of this study is to evaluate effects of human dry mandible motion on linear measurements and quality assessment via Cone Beam Computed Tomography. Although motion artifact is a common problem in daily pediatric diagnostic procedures, there are only few studies in the literatures on this topic. Subjects and Methods: l0 dry adult human edentulous mandibles were used in this invitro analytical study. Height, width and quality measured for three areas (midline, right posterior and left posterior) on each mandible. Three oral radiologists independently used a subjective rating score to evaluate the CBCT images. Obtained data analyzed via repeated measurements of variance LSD test and paired samples t test.Results: No significant statistical difference was observed in the assessment of jaw dimensions (height and width) with and without motion for three observers. But values were significant in the assessment of parameters due to quality between them. Conclusion: According to the data obtained from this study, we conclude that there is no significant statistical difference in assessment of jaw dimensions (height and width ) between three observers. Also, there is no significant statistical difference in the assessment of jaw dimension with and without motion, but observer's idea affects the quality of assessment.